2018
DOI: 10.1016/j.virol.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural proteins nsp2TF and nsp2N of porcine reproductive and respiratory syndrome virus (PRRSV) play important roles in suppressing host innate immune responses

Abstract: Recently, we identified a unique -2/-1 ribosomal frameshift mechanism in PRRSV, which yields two truncated forms of nonstructural protein (nsp) 2 variants, nsp2TF and nsp2N. Here, in vitro expression of individual PRRSV nsp2TF and nsp2N demonstrated their ability to suppress cellular innate immune responses in transfected cells. Two recombinant viruses were further analyzed, in which either nsp2TF was C-terminally truncated (vKO1) or expression of both nsp2TF and nsp2N was knocked out (vKO2). Host cellular mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 50 publications
2
62
0
Order By: Relevance
“…It has a single-stranded, positive-sense RNA genome of approximately 15.4 kb, which contains at least 10 open reading frames (ORFs), including ORF1a, ORF1b, ORF2a, ORF2b, ORF3, ORF4, ORF5, ORF5a, ORF6, and ORF7 (10,11). Viral proteases process polyproteins translated from ORF1a and ORF1b into 16 nonstructural proteins (Nsps): Nsp1␣/␤, Nsp2-6, Nsp7/7␣, Nsp8-12, Nsp2TF, and Nsp2N (12,13). It has been demonstrated that some of the Nsps are assembled with host cell components to form the viral replication and transcription complex (RTC) (14).…”
mentioning
confidence: 99%
“…It has a single-stranded, positive-sense RNA genome of approximately 15.4 kb, which contains at least 10 open reading frames (ORFs), including ORF1a, ORF1b, ORF2a, ORF2b, ORF3, ORF4, ORF5, ORF5a, ORF6, and ORF7 (10,11). Viral proteases process polyproteins translated from ORF1a and ORF1b into 16 nonstructural proteins (Nsps): Nsp1␣/␤, Nsp2-6, Nsp7/7␣, Nsp8-12, Nsp2TF, and Nsp2N (12,13). It has been demonstrated that some of the Nsps are assembled with host cell components to form the viral replication and transcription complex (RTC) (14).…”
mentioning
confidence: 99%
“…Arterivirus nsp2 was also reported to play an important role in the formation of double membrane vesicles (DMVs) that anchor the replication transcription complex (Snijder et al, 2001(Snijder et al, , 2013Posthuma et al, 2008). The identification of two additional frameshifting products, nsp2TF and nsp2N, increases the functional versatility and also the complexity of potential roles played by nsp2 (Snijder et al, 2013;Fang et al, 2012;Li et al, 2014Li et al, , 2018. We observed that all three nsp2-related proteins (nsp2, nsp2TF and nsp2N) are phosphorylated.…”
Section: Discussionmentioning
confidence: 93%
“…1). However, in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), we observed that the apparent sizes of nsp2-related proteins were substantially larger than the predicted molecular weights Li et al, 2018). We therefore investigated whether post-translational modifications, in particular phosphorylation, affect the mobilities of nsp2-related proteins in SDS-PAGE.…”
Section: Prrsv Nsp2-related Proteins Are Hyper-phosphorylatedmentioning
confidence: 99%
“…In addition, isoforms exist for PRRSV nsp2 that differ mainly in the C terminus, two of which (nsp2TF and nsp2N) are translated by a frameshift mechanism (16,17). The PLP2 domain contains catalytic sites that are highly conserved among arteriviruses; it possesses both cis-and trans-cleavage activities, which are responsible for nsp2/3 cleavage, and deubiquitinating activity, which likely plays an important role in regulating host innate immunity (14,(18)(19)(20)(21)(22)(23). The C-terminal TMD and CT are highly conserved and are required for PRRSV replication (15).…”
mentioning
confidence: 99%